2004
DOI: 10.1080/09723757.2004.11885903
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Exfoliated Oral Mucosal Cell Micronuclei Frequency in Normal, Precancerous and Malignant Epithelium

Abstract: Analysis of exfoliated buccal cell micronuclei (MN) is a sensitive method of monitoring genetic damage in the human population. In the present study 50 patients with precancerous or malignant oral epithelial lesions from the Departments of Facio-maxillary and ENT Surgery of RKMSP Hospital, Kolkata were compared with 50 age and sex matched healthy controls without any oral lesions.The MN frequency was increased in preoperative cancer cases and decreased in postoperative cases, while in pre cancerous cases it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
5
34
0
Order By: Relevance
“…These findings indicate a genotoxic damage of genotoxic agents and their metabolic products to exfoliated buccal epithelial cells. We found similar results in studies done by Parvathi et al and Halder et al [14,15] In the past, there are studies reported with significant micronuclei values in PMDs as compared to normal participants. In our study, we also found similar results.…”
Section: Discussionsupporting
confidence: 81%
“…These findings indicate a genotoxic damage of genotoxic agents and their metabolic products to exfoliated buccal epithelial cells. We found similar results in studies done by Parvathi et al and Halder et al [14,15] In the past, there are studies reported with significant micronuclei values in PMDs as compared to normal participants. In our study, we also found similar results.…”
Section: Discussionsupporting
confidence: 81%
“…The oral premalignant condition is defined as "a generalized state associated with a significantly increased risk of cancer." [4] Micronuclei (MN) are used as a biomarker for assessing damage to the cell for determination of population at risk. MN is studied from exfoliated buccal mucosa of smokers.…”
Section: Introductionmentioning
confidence: 99%
“…This could be achieved by detecting damage to DNA at a very early stage. Assessment of micronuclei has been a marker for genotoxic damage in assessment of nuclear changes in tobacco users as well as in development of premalignancies as shown in studies by Kayal et al 20 Suhas et al 21 Halder et al 22 Kamboj and Mahajan, 23 Sellappa et al 24 The present study showed a significant increase in number of micronuclei from healthy state to premalignancy to malignancy and reflects the findings of studies by Halder A et al 22 and Kamboj et al 23 However, in the present study there was no significant correlation between tobacco usage (frequency and duration) and the frequency of micronucleated oral mucosal cells which is contrary to the findings by Kayal et al 20 Halder et al 22 Kamboj et al 23 Gabriel et al 3 Palve et al 15 This questions the premise of cancer developing irrespective of genotoxic etiology. Presently, many cancers are seen to occur in the absence of a history of harmful habits while environmental pollution exposes people to carcinogens more frequently.…”
Section: Discussionmentioning
confidence: 99%